Efeitos dos esteróides anabólicos androgênicos sobre a bioquímica, morfologia, biomecânica e expressão gênica de diferentes tendões de ratos submetidos ao exercício de carga - Marqueti, Rita de Cássia (Universidade Federal de São Carlos, 2010)
The aim of this study was to evaluate the effects of vertical jump associated with anabolic androgenic steroids (AAS) on the biochemical, biomechanical and morphological properties, and the expression of the main genes responsible for remodeling in the calcaneal tendon (CT), superficial flexor tendon (TFS) and deep flexor tendon (TFP) in rats Animals were divided into four experimental groups: Sedentary (S), Trained (T) (vertical jump, 50 80% body weight load, 7 weeks, 5 days/week), AAS-treated sedentary rats (AAS) (5 mg/kg of body mass, twice a week).), and AAS-treated and trained animals (AAST). The techniques performed were: zymography (to analyze the metalopeptidase activity - MMP-2); biomechanical test (cross-sectional area, displacement at maximum load, maximum stress, maximum strain, and elastic modulus); morphology and real time PCR. The training promoted an increased in MMP-2 activity in the three regions of TFS, while the AAS treatment or the combination of training and AAS decreased both MMP-2 concentration and active form in all regions of the SFT. The biomechanical test showed that AAS increased tendon rigidity (i.e., lower elasticity and capacity to resist load) and the effects were enhanced by the combination of AAS and training. The DFT was the most affected by training, AAS, and the interaction of both. Take together the morphology and stereology showed that training increases the vascularity and cellularity, while the AAS combined with training reduced these two parameters in the three evaluated tendons. Gene expression showed that training did not increase the main genes expression responsible for tissue resistance: collagen type I and III, but the AAS or the association with training promoted a downregulation of expression in these genes on all tendons regions. In conclusion, the exercise increased remodeling and differently modulates the genes expression related to ECM remodeling in tendon. The AAS administration and combination with exercise induce negative effects, providing a poor remodeling and increasing risk of tendons injury.
Keywords: Fisiologia humana; Decanoato de nandrolona; Remodelamento do tendão; Metaloprotease; Biomecânica; Expressão gênica; Tendão; Esteróide anabólico androgênico; Remodelamento; Metalopeptidase de matrix; Teste biomecânico; Histologia; Tendon; Steroid anabolic androgenic; Remodeling; Matrix metallopeptidases; Biomechanical test; Histology; Gene expression; CIENCIAS BIOLOGICAS::FISIOLOGIA